Nano-modified composite fiber filter membrane based on HAP as well as preparation method and application of nano-modified composite fiber filter membrane

By adding surface-modified hydroxyapatite nanoparticles to the filter membrane, HAP nanomodified composite fiber filter membrane was prepared, which solved the problem of acidic substances generated by hydrolysis and aging of plant insulating oil, achieved efficient adsorption and intercepting acidic substances, extended the aging life of insulating oil and improved the insulation performance.

CN119656882AActive Publication Date: 2025-03-21GUANGDONG POWER GRID CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411818820.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Plant insulating oil is aging due to hydrolysis and aging during the operation of the transformer, resulting in a decrease in insulation performance and a shortened aging life.

Method used

Using a composite fiber filter membrane based on HAP nanomodified composite fiber membrane, a filter membrane with high specific surface area and significant surface effect was prepared by adding surface-modified hydroxyapatite nanoparticles to the filter membrane, which can efficiently adsorb and intercept aging acidic substances in plant insulating oils.

Benefits of technology

Effectively reduce the impurity content in plant insulating oil, reduce the dielectric loss factor and viscosity, extend the aging life, and improve the insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182574410000081
    Figure BDA0005182574410000081
Patent Text Reader

Abstract

The invention discloses an HAP-based nano-modified composite fiber filter membrane as well as a preparation method and application thereof, and relates to the field of insulating oil filtration treatment. The preparation method comprises the following steps: adding an alkali solution and 3-glycidyloxypropyltrimethoxysilane into hydroxyapatite nanoparticles to react to prepare surface-modified hydroxyapatite nanoparticles, then mixing and dispersing the surface-modified hydroxyapatite nanoparticles with PTFE powder and a dispersing agent to obtain a spinning solution, and preparing the composite fiber filter membrane by adopting an electrostatic spinning machine. The composite fiber filter membrane prepared by the invention is doped with the surface modified hydroxyapatite nanoparticles, can efficiently adsorb aged acidic substances in the vegetable insulating oil, and meanwhile, the filter membrane intercepts and captures other micro impurities, so that the content of impurities in the vegetable insulating oil is effectively reduced, and purification is realized; therefore, the dielectric loss factor and viscosity of the vegetable insulating oil are reduced, the aging life is prolonged, and the insulating property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of insulating oil filtration treatment, and in particular to a HAP-based nano-modified composite fiber filter membrane and a preparation method and application thereof. Background Art

[0002] Vegetable insulating oil is an insulating oil extracted from natural oil crops such as soybeans, rapeseed, coconut, etc. It has the characteristics of high ignition point, renewable, biodegradable and non-toxic. It is considered to be a green and environmentally friendly liquid insulating medium with excellent electrical and physical and chemical properties. It has been successfully used in distribution transformers.

[0003] However, during the operation of the transformer, it is difficult to avoid contact with air. Vegetable insulating oil has strong hydrophilicity and can absorb more water, which will accelerate the aging of the insulating oil, causing the vegetable insulating oil to hydrolyze and generate a large amount of acidic substances. These moisture and acidic substances will affect the aging life of the insulating oil, greatly accelerate the increase in the viscosity of the vegetable insulating oil, and cause the thermal conductivity to decrease, thereby greatly deteriorating the insulation performance of the vegetable insulating oil. Summary of the invention

[0004] The present invention provides a HAP nano-modified composite fiber filter membrane and a preparation method and application thereof, which can accurately filter impurities in vegetable insulating oil aged by hydrolysis, intercept and adsorb aged acidic substances, reduce the dielectric loss factor of the vegetable insulating oil, and increase the aging life.

[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a HAP nano-modified composite fiber filter membrane, comprising the following steps:

[0006] (1) adding an alkaline solution and 3-glycidyloxypropyltrimethoxysilane to hydroxyapatite nanoparticles, heating, stirring and dispersing the mixture uniformly, cooling the mixture to room temperature, filtering the mixture, washing, drying, crushing and sieving the mixture to obtain surface-modified hydroxyapatite nanoparticles;

[0007] (2) adding PTFE powder into a container containing a dispersant, stirring evenly, adding surface-modified hydroxyapatite nanoparticles, stirring until clear and transparent, and then letting it stand for degassing to obtain a spinning solution;

[0008] (3) Adding the spinning solution into an electrospinning machine and spinning to prepare a composite fiber filter membrane.

[0009] By adopting the above scheme, the composite fiber filter membrane prepared in the present application has an extremely high specific surface area and its surface effect is more significant. The added surface-modified hydroxyapatite nanoparticles can efficiently adsorb aging acidic substances produced by hydrolysis in the vegetable insulating oil, purify the acid produced by hydrolysis in the aged vegetable insulating oil, and adsorb and capture other micro impurities, which can reduce the impurity content in the vegetable insulating oil, thereby more effectively reducing the dielectric loss factor and viscosity of the vegetable insulating oil, and improving the aging life.

[0010] As a preferred embodiment, in step (1), the mass ratio of the hydroxyapatite nanoparticles, the alkaline solution, and 3-glycidyloxypropyltrimethoxysilane is (4-5):10:1.

[0011] As a preferred embodiment, the mass ratio of the PTFE powder to the dispersant is 1:(12-14); the mass ratio of the surface-modified hydroxyapatite nanoparticles to the PTFE powder is 1:(10-14).

[0012] As a preferred embodiment, the dispersant is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and polydimethylsiloxane.

[0013] As a preferred embodiment, in step (1), the mesh size of the surface-modified hydroxyapatite nanoparticles is 100-500 mesh.

[0014] As a preferred embodiment, in step (1), the heating temperature is 80-100° C., the stirring and dispersing time is 2-6 h, and washing is performed with water and ethanol in sequence.

[0015] As a preferred embodiment, in step (2), the PTFE powder and the surface-modified hydroxyapatite nanoparticles are pre-dried at 50-70° C. for 15-20 h.

[0016] As a preferred embodiment, in step (2), the stirring temperature is 30-40°C, the stirring rate is 350-400 r / min, and the standing degassing time is 6-8 h.

[0017] As a preferred embodiment, in step (3), the temperature inside the electrospinning machine box is controlled at 35-40°C, and the humidity is controlled at 35%-37%. The spinning solution is slowly sucked into a 10mL syringe, and the bubbles in the syringe are fully removed. A stainless steel needle is used and connected to a positive high-voltage DC source. A flat-plate collector is connected to a negative high-voltage DC source. A conductive adhesive is used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe is controlled to be 18cm, and the pushing speed of the syringe is 0.75-0.85mL / h.

[0018] As a preferred solution, the concentration of the alkaline solution is 4-6 mol / L.

[0019] In order to solve the above technical problems, the second purpose of the present invention is to provide a HAP-based nano-modified composite fiber filter membrane.

[0020] In order to solve the above technical problems, the third object of the present invention provides an application of a HAP nano-modified composite fiber filter membrane in purifying vegetable insulating oil.

[0021] As a preferred solution, the method comprises the following steps: cutting the composite fiber filter membrane and installing it on a sand core, vacuum filtering the vegetable insulating oil, and setting the vacuum degree to 0.02-0.05 MPa.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The composite fiber filter membrane prepared in the present application has extremely high hydrophobicity, and the doped surface-modified hydroxyapatite nanoparticles can efficiently adsorb aging acidic substances in vegetable insulating oil, while efficiently intercepting and capturing other micro impurities, effectively reducing the impurity content in the vegetable insulating oil to achieve purification, thereby more effectively reducing the dielectric loss factor and viscosity of the vegetable insulating oil, and improving the aging life and insulation performance. DETAILED DESCRIPTION

[0024] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. Unless otherwise specified, the raw materials used in this application can be obtained commercially, and the same raw materials are used in the parallel experiments.

[0025] Polytetrafluoroethylene comes from Daikin Industries, Ltd. of Japan, model DAIKIN PTFE L-5F;

[0026] Polyvinylidene fluoride comes from Shanghai Sanaifu New Material Technology Co., Ltd., model FR904, molecular weight 200000.

[0027] Example 1

[0028] A HAP nano-modified composite fiber filter membrane, the preparation method of which comprises the following steps:

[0029] (1) A 5 mol / L NaOH aqueous solution and 3-glycidyloxypropyltrimethoxysilane (GPS) were added to hydroxyapatite nanoparticles (HAP), wherein the mass ratio of the hydroxyapatite nanoparticles, the NaOH aqueous solution, and the 3-glycidyloxypropyltrimethoxysilane (GPS) was 5:10:1, and ultrasonic stirring was performed at room temperature for 1 hour to obtain a stable dispersion, and then the dispersion was heated to 90°C and stirred for 1 hour to be fully mixed. After cooling to room temperature, the dispersion was filtered, and the solid was washed with deionized water and anhydrous ethanol until it was neutral. The surface-modified hydroxyapatite nanoparticles of 200 mesh were obtained after drying, crushing, and sieving.

[0030] (2) placing polytetrafluoroethylene (PTFE) powder and surface-modified hydroxyapatite nanoparticles in a vacuum drying oven for 15 h at a drying temperature of 50°C;

[0031] (3) N,N-dimethylacetamide (DMAc) dispersant is placed in a glass bottle and placed on a magnetic stirrer at a temperature of 30°C and a stirring speed of 380 r / min. PTFE powder is slowly poured into the stirred dispersant, and the mass ratio of PTFE powder to N,N-dimethylacetamide dispersant is 1:13. During the stirring process, the glass bottle is sealed to reduce the volatilization of the solvent. Surface-modified hydroxyapatite nanoparticles are poured into the dispersed solvent during the stirring process, and the mass ratio of surface-modified hydroxyapatite nanoparticles to PTFE powder is 1:11. After stirring until the mixed solution is clear and transparent, it is placed in a vacuum drying oven and allowed to stand for degassing for 6 hours to obtain a spinning solution;

[0032] (4) The temperature inside the WL-2C high-voltage electrospinning machine was controlled at 35°C and the humidity was controlled at 35%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 18 cm. The pushing speed of the syringe was 0.75 mL / h to prepare a composite fiber filter membrane.

[0033] Example 2

[0034] A HAP nano-modified composite fiber filter membrane, the preparation method of which comprises the following steps:

[0035] (1) A 5 mol / L NaOH aqueous solution and 3-glycidyloxypropyltrimethoxysilane (GPS) were added to hydroxyapatite nanoparticles (HAP), wherein the mass ratio of the hydroxyapatite nanoparticles, the NaOH aqueous solution, and the 3-glycidyloxypropyltrimethoxysilane (GPS) was 5:10:1, and ultrasonic stirring was performed at room temperature for 2 h to obtain a stable dispersion, and then the dispersion was heated to 90° C. and stirred for 2 h to be fully mixed, and then the dispersion was filtered after cooling to room temperature, and the solid was washed with deionized water and anhydrous ethanol until it was neutral, and then dried, crushed, and sieved to obtain 200-mesh surface-modified hydroxyapatite nanoparticles;

[0036] (2) PTFE powder and surface-modified hydroxyapatite nanoparticles were placed in a vacuum drying oven and dried for 17 h at a drying temperature of 60°C;

[0037] (3) N,N-dimethylacetamide (DMAc) dispersant is placed in a glass bottle and placed on a magnetic stirrer at a temperature of 35°C and a stirring speed of 390 r / min. PTFE powder is slowly poured into the stirred dispersant, and the mass ratio of PTFE powder to N,N-dimethylacetamide dispersant is 1:12. During the stirring process, the glass bottle is sealed to reduce the volatilization of the solvent. Surface-modified hydroxyapatite nanoparticles are poured into the dispersed solvent during the stirring process, and the mass ratio of surface-modified hydroxyapatite nanoparticles to PTFE powder is 1:10. After stirring until the mixed solution is clear and transparent, it is placed in a vacuum drying oven and allowed to stand for degassing for 7 hours to obtain a spinning solution;

[0038] (4) The temperature inside the WL-2C high-voltage electrospinning machine was controlled at 38°C and the humidity was controlled at 36%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 18 cm. The pushing speed of the syringe was 0.8 mL / h to prepare a composite fiber filter membrane.

[0039] Example 3

[0040] A HAP nano-modified composite fiber filter membrane, the preparation method of which comprises the following steps:

[0041] (1) A 5 mol / L NaOH aqueous solution and 3-glycidyloxypropyltrimethoxysilane (GPS) were added to hydroxyapatite nanoparticles (HAP), wherein the mass ratio of the hydroxyapatite nanoparticles, the NaOH aqueous solution, and the 3-glycidyloxypropyltrimethoxysilane (GPS) was 5:10:1, and ultrasonic stirring was performed at room temperature for 3 h to obtain a stable dispersion, and then the dispersion was heated to 90° C. and stirred for 3 h to be fully mixed, and then the dispersion was filtered after being cooled to room temperature, and the solid was washed with deionized water and anhydrous ethanol until it was neutral, and then dried, crushed, and sieved to obtain 200-mesh surface-modified hydroxyapatite nanoparticles;

[0042] (2) PTFE powder and surface-modified hydroxyapatite nanoparticles were placed in a vacuum drying oven and dried for 20 h at a drying temperature of 70°C;

[0043] (3) N,N-dimethylacetamide (DMAc) dispersant is placed in a glass bottle and placed on a magnetic stirrer at a temperature of 40°C and a stirring speed of 400 r / min. PTFE powder is slowly poured into the stirred dispersant, and the mass ratio of PTFE powder to N,N-dimethylacetamide dispersant is 1:14. During the stirring process, the glass bottle is sealed to reduce the volatilization of the solvent. Surface-modified hydroxyapatite nanoparticles are poured into the dispersed solvent during the stirring process, and the mass ratio of surface-modified hydroxyapatite nanoparticles to PTFE powder is 1:12. After stirring until the mixed solution is clear and transparent, it is placed in a vacuum drying oven and allowed to stand for degassing for 8 hours to obtain a spinning solution;

[0044] (4) The temperature inside the WL-2C high-voltage electrospinning machine was controlled at 40°C and the humidity was controlled at 37%. The spinning solution was slowly sucked into a 10 mL syringe and the bubbles in the syringe were fully removed. A stainless steel needle was used and connected to a positive high-voltage DC source. The flat-plate collector was connected to a negative high-voltage DC source. A conductive adhesive was used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe was controlled to be 18 cm. The pushing speed of the syringe was 0.85 mL / h to prepare a composite fiber filter membrane.

[0045] Example 4

[0046] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the mass ratio of hydroxyapatite nanoparticles, NaOH aqueous solution and 3-glycidyloxypropyltrimethoxysilane (GPS) is 4:10:1.

[0047] Example 5

[0048] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), the mass ratio of surface-modified hydroxyapatite nanoparticles to PTFE powder is 1:14.

[0049] Comparative Example 1

[0050] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (3), the amount of surface-modified hydroxyapatite nanoparticles added is 0.

[0051] Comparative Example 2

[0052] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), 5 mol / L NaOH solution is replaced by an equal amount of 5 mol / L HCl solution.

[0053] Comparative Example 3

[0054] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (1), hydroxyapatite nanoparticles are replaced by silicon dioxide nanoparticles in equal amounts.

[0055] Comparative Example 4

[0056] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in steps (2) and (3), PTFE powder is replaced by polyvinylidene fluoride in an equal amount.

[0057] Comparative Example 5

[0058] A HAP-based nano-modified composite fiber filter membrane, wherein each step of the preparation method and the reagents, equipment and process parameters used in each step are the same as those in Example 1, except that in step (3), the mass ratio of surface-modified hydroxyapatite nanoparticles to PTFE powder is 1:15.

[0059] Application Examples 1-5 and Comparative Application Examples 1-5

[0060] An application of HAP nano-modified composite fiber filter membrane in purifying aged plant transformer insulating oil comprises the following steps:

[0061] The composite fiber filter membrane prepared in the embodiment or comparative example is cut into membrane samples with a diameter of 4 cm and installed on a sand core. The FR3 soybean vegetable insulating oil is vacuum filtered, with 400 mL filtered at a time. The vacuum degree of the circulating vacuum water pump connected to the filtration device is set to 0.03 MPa. The viscosity, acid value and dielectric loss factor of the vegetable oil sample before and after filtration are measured.

[0062] Application Example 6

[0063] An application of HAP nano-modified composite fiber filter membrane in purifying aged plant transformer insulating oil comprises the following steps:

[0064] The composite fiber filter membrane prepared in Example 1 was cut into membrane samples with a diameter of 4 cm and installed on a sand core. Karamay No. 25 mineral insulating oil was vacuum filtered, with 400 mL filtered at a time. The vacuum degree of the circulating vacuum water pump connected to the filtration device was set to 0.03 MPa. The viscosity, acid value and dielectric loss factor of the vegetable oil samples before and after filtration were measured.

[0065] Performance testing

[0066] 1. Viscosity: Application Examples and Comparative Application Examples The viscosity of the insulating oil was measured by a DN-79 rotational viscometer at a temperature of 40°C. The test results are shown in Table 1 below.

[0067] 2. Acid value: Application examples and comparative application examples The acid value content in insulating oil was tested according to GB / T 28552-2012 standard. The test results are shown in Table 1 below.

[0068] 3. Dielectric loss factor: Application examples and comparative application examples The dielectric loss factor of insulating oil is tested according to GB / T5654-2007 standard. The test results are shown in Table 1 below.

[0069] 4. Water drop contact angle: Refer to GB / T 30693-2014 standard and use SDC-100 contact angle meter to measure the contact angle of the composite fiber filter membrane used in the corresponding use case and comparative application example. Drop water on the surface of the composite fiber filter membrane and measure the contact angle formed by the water drop on the surface of the composite fiber filter membrane.

[0070] Table 1 - Performance test results of application examples and comparative application examples before and after filtration of aged insulating oil

[0071]

[0072] As shown in Table 1, by comparing the schemes of Application Example 1 and Comparative Application Examples 1 and 3, it can be seen that Comparative Example 1 does not add surface-modified hydroxyapatite nanoparticles, and Comparative Example 3 adds modified silica nanoparticles. The viscosity and acid value of the vegetable insulating oil after filtration do not change much, and the prepared composite fiber filter membrane has low hydrophobicity, insufficient adsorption capacity for aged acidic substances in the insulating oil, and poor interception effect, resulting in a high dielectric loss factor of the vegetable insulating oil; the composite fiber filter membrane prepared in Example 1 of the present application is doped with surface-modified hydroxyapatite nanoparticles, has ultra-high hydrophobicity and filtration accuracy, can adsorb a large amount of acidic substances in the insulating oil, adsorb and intercept impurities such as acidic aging products in the vegetable insulating oil, purify the acid produced by hydrolysis in the aged vegetable insulating oil, and adsorb and capture other micro impurities, thereby more effectively reducing the acid value, dielectric loss factor and viscosity of the vegetable insulating oil.

[0073] As shown in Table 1, by comparing the schemes of Application Example 1 and Comparative Application Example 6, it can be seen that the composite fiber filter membrane prepared in Example 1 of the present application is used to filter aged vegetable insulating oil and mineral insulating oil respectively. It can be found that the acid value in the vegetable insulating oil decreases to a greater extent and the viscosity decreases significantly, so that the dielectric loss factor of the vegetable insulating oil decreases, while the acid value and viscosity in the mineral insulating oil decrease to a lesser extent. Although the dielectric loss factor decreases, the decrease is not as large as that in Application Example 1, indicating that the purification effect of the composite fiber filter membrane of the present application on aged mineral insulating oil is not as good as that of vegetable insulating oil, and the capture efficiency of moisture and acidic substances generated by hydrolysis of vegetable insulating oil is better.

[0074] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a HAP nano-modified composite fiber filter membrane, characterized in that: The following steps are involved: (1) adding an alkaline solution and 3-glycidyloxypropyltrimethoxysilane to hydroxyapatite nanoparticles, heating, stirring and dispersing the mixture uniformly, cooling the mixture to room temperature, filtering the mixture, washing, drying, crushing and sieving the mixture to obtain surface-modified hydroxyapatite nanoparticles; (2) adding PTFE powder into a container containing a dispersant, stirring evenly, adding surface-modified hydroxyapatite nanoparticles, stirring until clear and transparent, and then letting it stand for degassing to obtain a spinning solution; (3) Adding the spinning solution into an electrospinning machine and spinning to prepare a composite fiber filter membrane.

2. The method for preparing a HAP nano-modified composite fiber filter membrane according to claim 1, characterized in that: In step (1), the mass ratio of the hydroxyapatite nanoparticles, the alkaline solution, and 3-glycidyloxypropyltrimethoxysilane is (4-5):10:

1.

3. The method for preparing a HAP nano-modified composite fiber filter membrane according to claim 1, characterized in that: The mass ratio of the PTFE powder to the dispersant is 1:(12-14); the mass ratio of the surface-modified hydroxyapatite nanoparticles to the PTFE powder is 1:(10-14).

4. The method for preparing a HAP nano-modified composite fiber filter membrane according to claim 1, characterized in that: The dispersant is at least one of N,N-dimethylformamide, N,N-dimethylacetamide and polydimethylsiloxane.

5. The method for preparing a HAP nano-modified composite fiber filter membrane according to claim 1, characterized in that: In step (1), the mesh size of the surface-modified hydroxyapatite nanoparticles is 100-500 meshes.

6. The method for preparing a HAP nano-modified composite fiber filter membrane according to claim 1, characterized in that: Satisfy at least one of the following a)-c): a) In step (1), the heating temperature is 80-100°C, the stirring and dispersing time is 2-6h, and water and ethanol are used for washing in sequence; b) in step (2), the PTFE powder and the surface-modified hydroxyapatite nanoparticles are dried at 50-70° C. for 15-20 h in advance; c) In step (2), the stirring temperature is 30-40°C, the stirring rate is 350-400 r / min, and the standing degassing time is 6-8 h; d) In step (3), the temperature inside the electrospinning machine is controlled at 35-40°C, and the humidity is controlled at 35%-37%. The spinning solution is slowly sucked into a 10 mL syringe, and the bubbles in the syringe are fully removed. A stainless steel needle is used and connected to a positive high-voltage DC source. A flat-plate collector is connected to a negative high-voltage DC source. A conductive adhesive is used to stick tin foil to the flat-plate collector. The distance between the flat-plate collector and the syringe is controlled to be 18 cm. The pushing speed of the syringe is 0.75-0.85 mL / h.

7. The method for preparing a HAP nano-modified composite fiber filter membrane according to claim 1, characterized in that: The concentration of the alkaline solution is 4-6 mol / L.

8. A HAP-based nano-modified composite fiber filter membrane prepared by the method for preparing a HAP-based nano-modified composite fiber filter membrane as described in any one of claims 1 to 7.

9. Use of the HAP nano-modified composite fiber filter membrane as claimed in claim 8 in purifying vegetable insulating oil.

10. The use of a HAP nano-modified composite fiber filter membrane in purifying vegetable insulating oil according to claim 9, characterized in that: The method comprises the following steps: cutting the composite fiber filter membrane and installing it on a sand core, vacuum filtering the vegetable insulating oil, and setting the vacuum degree to 0.02-0.05MPa.

Citation Information

Patent Citations

  • Oil-water separation fiber membrane

    CN105908364A

  • Nano-HAP / PVDF hybrid film, and preparation method and application thereof

    CN108636138A

  • Functional PAN-HAP nanofiber membrane and preparation method thereof

    CN110923953A

  • Ultrafiltration membrane for removing fluoride in water body, and preparation method and application thereof

    CN111974232A

  • Composite nanofiber membrane as well as preparation method and application thereof

    CN115976740A